Early BCR Events and Antigen Capture, Processing, and Loading on MHC Class II on B Cells - Avalos, Ana M.; Ploegh, Hidde (Frontiers in Immunology, 2014)
B cells are efficient antigen presenting cells (APCs) by means of antigen uptake through the B cell receptor (BCR). The mechanism of antigen recognition remains a topic of debate; while the prevalent view holds that antigens need to be multivalent for BCR activation, monovalent antigens can also initiate B cell responses. In this review we describe the steps required for antigen uptake, processing and loading onto MHC Class II compartments in B cells for efficient presentation to CD4 T cells, with a special focus in the initial steps of BCR recognition of antigen.